Can lymph node involvement in unilateral Wilms tumor be predicted by preoperatively known data in combination with intraoperative findings? - Meier, Clemens-Magnus; Furtwängler, Rhoikos; Welter, Nils; Mergen, Marvin; Wagenpfeil, Stefan; von Schweinitz, Dietrich; Stein, Raimund; Kager, Leo; Schenk, Jens-Peter; Vokuhl, Christian; Kroiss-Benninger, Sabine; Melchior, Patrick; et al. (Annals of surgery, 2026)
Objective:  - This study aimed to identify parameters that allow the estimation of tumor-infiltrated lymph nodes (LN) after pretreatment for unilateral Wilms tumor (WT). - Background:  - Complete tumor resection with removal of regional LN is always necessary. Positive LNs require local irradiation influencing benefits in the case of NSS in long-term follow-up. Clinical and tumor-related data available at the time of surgery, in combination with intraoperative abdominal findings (IAF), were used to estimate the LN status during surgery. - Methods:  - Altogether, 2115 patients with unilateral WT were prospectively enrolled in SIOP-93-01 / GPOH and SIOP-2001 / GPOH over a period of 30 years (1993-2023). LN infiltration by tumor was calculated for age, sex, metastases at diagnosis, tumor volume (TV), TV shrinkage, and IAF using logistic regression models. - Results:  - Age ≥48 months (P<0.001, OR: 2.17, CI: 1.57-3.00), TV at diagnosis ≥300 (P<0.001, OR: 3.72, CI: 2.37-5.85), metastasis at diagnosis (P<0.001, OR: 6.21, CI: 4.47-8.62) and IAF (>1: P<0.001, OR: 3.54, CI: 2.13-5.88) correlated with positive LNs. TV shrinkage was not predictive of positive LN. Three flow charts were developed based on age, TV at diagnosis, metastasis, and IAF. These flowcharts defined risks between 0% and 41.5% for LN infiltration by tumor. - Conclusions:  - The combination of age, TV at diagnosis, and metastasis with IAF allows the estimation of the frequency of positive LNs, which may help surgeons decide about NSS.
Gesehen am 23.02.2026